Hubungan Antara Kecerdasan Emosional dan Kenakalan Remaja Pada Siswa SMK Negeri 1 Samigaluh Kabupaten Kulon Progo - Yohannes Tua Tambunan; FX Wahyu Widiantoro; Indra Wahyudi (LPPM Universitas Proklamasi 45, 2024)
This study aims to find out the relationship between emotional intelligence and juvenile delinquency in Vocational High School 1 Samigaluh students. The hypothesis in this study is that there is a negative relationship between emotional intelligence and adolescent behavior. Subjects in this study were 50 people aged between 15 and 18. The data gathering tools used are the emotional intelligence adaptation scale compiled by Fitri Eka Wardani (2012) and the adolescent behavior scale composed by Elliot and Ageton. (1980). The data analysis techniques used are simple regression analysis techniques. The results of this study resulted in a regression coefficient value of -433, which means emotional intelligence has a negative impact on adolescent behavior. This means that the higher the level of emotional intelligence, will make the lower of juvenile delinquency.